Perceived relationships between severity of psoriasis symptoms, gender, stigmatization and quality of life. (14th February 2012) - Böhm, D.; Stock Gissendanner, S.; Bangemann, K.; Snitjer, I.; Werfel, T.; Weyergraf, A.; Schulz, W.; Jäger, B.; Schmid‐Ott, G.
Abstract: Background Psoriasis is a skin disease with negative physical, psychological and social repercussions for those affected, but we still lack knowledge of how somatic and non‐somatic factors directly and indirectly combine to affect patients' quality of life (QoL). Objectives This study seeks a better understanding of the relations between symptom severity, discomfort, stigmatization, gender and QoL among psoriasis patients. Methods The sample comprised 381 psoriasis patients in inpatient care. Symptom severity and discomfort were measured subjectively with single items. Stigmatization was measured with the Questionnaire on Experience with Skin Complaints. QoL was measured using the Dermatology Life Quality Index (DLQI) and the Short Form‐8 Health Survey (SF‐8). Results Symptom severity was associated with higher discomfort, stigmatization and lower skin‐related QoL. Symptom severity correlated weakly with more general aspects of QoL as measured by the SF‐8. Men and women reported different experiences with discomfort, stigmatization and mental aspects of QoL (SF‐8 mental component summary score). Some stigmatization parameters function as mediating variables between symptom severity and QoL. Conclusions Our findings suggest that the effect of stigmatization on skin‐related QoL is driven by symptom severity and stigmatization combined, whereas its effect on mental health is driven mostly by stigmatization alone. Further, although women and men experience the social impact of psoriasis differently, the effect of stigmatization on QoL is similar for both genders.